Construções encaixadas na linguagem infantil : emergência e uso - Amorim, Carmelita Minelio da Silva (2007)
Several linguistic studies about the process of language acquisition have been reached space in the linguistic field, although the research about operation and development of language from children's speech in incipient stage to be considered a great challenge. This dissertation focuses the morphsyntax aspect where refers to the path of the fitted constructions, considering structural and pragmatic-discursive aspects. For that, we analyzed, in samples of children's speech among the age 1 year and 7 months until 6 years old, the emersion and development of those constructions. In the analysis, we conjugated data of longitudinal and stratified characters, in order to provide more certainty about the phenomenon. The analysis of embedded clauses allows to observe that those constructions follow a functional course from the pragmatic way to the syntactic way of communication, because the occurrences, in the initial stages of acquisition suffer influences from pragmatic elements which are involved in the immediate context of communication and forms become more complex while the child moves forward in the acquisition process. Also, we can be observed the passage of value [+concrete] to value [- concrete] in the linguistic items that appear in the usage that children do of embedded clauses.